It takes a candidate : why women don't run for office - Lawless, Jennifer L., 1975- (Cambridge University Press, 2005)
Serving as the first systematic, nationwide empirical account of the manner in which gender affects political ambition, and based on data from the Citizen Political Ambition Study, a national survey conducted on almost 3,800 potential candidates, this looks at why women are less likely than men to demonstrate political ambition.